Clinical and histopathological study of postinflammatory hypopigmented macular skin lesions - Hogade, Ashok S.; Sri Hari Reddy, N. (International Journal of Research in Dermatology, 2019)
Background: The objective of the study was to study the various etiologies and ascertain different clinicalpresentations of post-inflammatory hypopigmented lesions. Age and sex distribution, socio economic status, seasonal incidence, most common to rare variants amongst all conditions and to correlate them histopathologically. Methods: 100 patients presenting with Post-inflammatory hypopigmented lesions were selected and detailed history and examination was done. Lab investigations and histopathology was done in those cases. Results: Among the various causes of post-inflammatory hypopigmentation, commonly observed conditions were Pityriasis versicolor, mechanical injuries, Pityriasis alba, burns, leprosy, allergic contact dermatitis, morphoea, discoid lupus erythematosus, psoriasis and Steven’s Johnson syndrome. Most common age group affected was in 21-30 years of age. Males (60%) were more than females (40%). People of lower socioeconomic status (55%) presented with post-inflammatory hypo pigmented lesions commonly. History of hypopigmentation ranged from 0-6 months in majority of cases. Upper limbs, trunk and face and neck regions were the most common sites involved. Commonest etiology amongst all cases was pityriasisversicolor, followed by mechanical injuries, PityriasisAlba and burns. Clinical diagnosis correlated with histopathology in these cases. Conclusions: The study concluded that post-inflammatory hypopigmented lesions presented with various manifestations, more common in young, male adults, common in people of lower socioeconomic group. Upper limbs, trunk and face and neck are the common sites involved and histopathology correlated with clinical diagnosis in many cases.